Implementation of STAND Type Cooperative Learning Model Assisted by Kahoot Media to Increase Motivation in History Subjects for Class X.12 SMA Negeri 5 Medan - Akmarina, Nur; Nasution, Abd Haris; Nasution, Sovianur (Jurnal Akuntansi Hukum dan Edukasi, 2024)
This study aims to improve students' learning motivation in history subjects by implementing of STAND Type Cooperatif learning model assisted by Kahoot Media at SMA Negeri 5 Medan. This research method adopts a qualitative approach by collecting data through questionnaires and observing student activities.. Cycle I showed poor results with a presentation of 60%, but in cycle II there was a significant increase with a presentation of 93%. The findings from this study show that application of this learning model and media has succeeded in increasing students' motivation in learning history subjects.